Front Cover: Isotropic Scalar Quantum Sensing of Magnetic Fields for Industrial Application (Adv. Quantum Technol. 8/2020). Issue 8 (4th August 2020) - Staacke, Robert; John, Roger; Wunderlich, Ralf; Horsthemke, Ludwig; Knolle, Wolfgang; Laube, Christian; Glösekötter, Peter; Burchard, Bernd; Abel, Bernd; Meijer, Jan
Abstract : The cover shows a variety of diamond nanoparticles with a high concentration of nitrogen‐vacancy centers. The bright red fluorescence of these particles depends on the strength of the magnetic field represented by field lines. With a stronger magnetic field the fluorescence is quenched due to spin mixing. Additionally, the field direction dependency is averaged out through the number of nanoparticles. This enables the creation of a robust isotropic quantum sensor for magnetic fields, as demonstrated by Robert Staacke and co‐workers in article number 2000037 .